'Io so': the absence of resolution as resolution in contemporary Italian cinema about the 'years of lead'. Issue 2 (18th May 2017) - Lichtner, Giacomo
Abstract : This article analyses three fantasy sequences in contemporary Italian cinema about political terrorism in the period known as the anni di piombo ('years of lead'). It argues that, faced with divided memories, ideologically-charged narratives of the past, political interference and the so-called Italian anomalies, film-makers have reacted by making the absence of resolution a question in its own right. The article identifies and analyses three specific approaches, each linked to a sequence from each film. The first sequence, ' uno sfondo di verità ', focuses on Marco Tullio Giordana's Romanzo di una strage, which navigates the absence of resolution, lamenting it but also exploiting it to force a particular version of events. The second sequence, ' vado a dormire ', focuses on Marco Bellocchio's Buongiorno, notte, which uses a dream sequence to fabricate a different resolution, but simultaneously underscore reality. The third sequence, ' mea culpa ', analyses the invented confession scene in Paolo Sorrentino's Il Divo, arguing that it employs ambiguity to find closure in imagination itself, rather than in an imagined truth. Through the micro-analyses of these texts, this article seeks to highlight a broader question about cinema's relationship with ambiguity and mystery in modern Italian history. Italian summary: Questo articolo analizza tre sequenze, tratte dal cinema contemporaneo sugli anni di piombo, che utilizzano l'invenzione per avvicinarsi alla storia per molti versi ancora misteriosa di quegli anni. La tesi centrale dell'articolo è che, a fronte di memorie divise, costruzioni del passato politicizzate, interferenze politiche e le cosiddette anomalie italiane, i cineasti hanno reagito concentrandosi sull'assenza di risoluzione. L'articolo identifica tre modelli, ciascuno incarnato da una sequenza: ' uno sfondo di verità ', basato sulla conversazione tra Calabresi e d'Amato in Romanzo di una strage di Marco Tullio Giordana; ' vado a dormire ', tratto dal doppio finale di Buongiorno, notte di Marco Bellocchio; e ' mea culpa ', che si rifà alla confessione di Andreotti in Il Divo di Paolo Sorrentino. Il primo cerca di risolvere il mistero, ma anche di sfruttarlo per cercare una lettura condivisa del passato; il secondo immagina una risoluzione alternativa, che ha la funzione di rinforzare la reale conclusione storica degli eventi; il terzo, intrinsicamente post-moderno, non trova la soluzione all'ambiguità attraverso un'invenzione ma piuttosto nell'atto stesso di inventare. Attraverso queste tre micro-analisi del testo, questo aritcolo cerca di pore una domanda più ampia sul cinema come interfaccia tra memoria, ambiguità e mistero nella storia dell'Italia moderna.